Novel Quinazoline Moiety: Synthesis, In-Vitro Biological Evaluation and Molecular Modelling Studies - Sodhi, Jaspreet Kaur; Aggarwal, Babita; Kumari, Babita; Hindwal, Palak; Yadav, Manoj Kumar; Singh, Surjeet; Singh, Ritu; Sharma, Prashant; Samyal, Manish; Prasad, Triloki (Journal of Neonatal Surgery, 2025)
The quinazoline core has emerged as a favorable scaffold for the development of novel EGFR inhibitors due to increased affinity for the active site of EGFR kinase. Currently, there are five first-generation (gefitinib, erlotinib, lapatinib, vandetanib) and two second-generation (afatinib and dacomitinib) quinazoline-based EGFR inhibitors approved for the treatment of various types of cancers. The aim of this review is to outline the structural modulations favorable for the inhibitory activity toward both common mutant (del19 and L858R) and resistance-conferring mutant (T790M and C797S) EGFR forms, and provide an overview of the newly synthesized quinazoline derivatives as potentially competitive, covalent or allosteric inhibitors of EGFR